Legal Framework for Addressing Sea Environmental Pollution: A Case Study of the Montara Oil Spill in East Timor - Mahendra, Brian Maulana; Lien, Pao Thai; Myat, Champo Khan (International Law Discourse in Southeast Asia, 2024)
This study delves into the legal framework pertinent to addressing sea environmental pollution, with a specific focus on the Montara Oil Spill incident in East Timor. The Montara Oil Spill presents a compelling case study, highlighting the complexities and challenges associated with responding to marine environmental disasters. By examining international conventions, regional agreements, and domestic laws, this research seeks to evaluate the adequacy of existing legal frameworks in managing sea pollution incidents effectively. Furthermore, it aims to assess the efficacy of regulatory mechanisms in holding accountable those responsible for environmental harm and ensuring appropriate compensation for affected parties. Through a comprehensive analysis of legal doctrines, relevant case law, and policy considerations, this study aims to offer valuable insights into enhancing the legal framework for mitigating and preventing sea environmental pollution. By synthesizing findings from diverse sources, including international treaties, national legislation, and jurisprudential trends, this research endeavors to identify areas for improvement in regulatory frameworks and enforcement mechanisms. Additionally, it seeks to explore opportunities for strengthening international cooperation and collaboration in safeguarding marine ecosystems and addressing transboundary pollution issues. Ultimately, this study contributes to the broader discourse on environmental law and policy by shedding light on the legal dimensions of sea pollution management. By critically examining the Montara Oil Spill case and drawing lessons from it, this research seeks to inform future regulatory developments and advocacy efforts aimed at promoting environmental sustainability and protecting the world's oceans.